Spatial Variation in the Origin of Dissolved Organic Carbon in Snow on the Juneau Icefield, Southeast Alaska - Fellman, Jason B.; Hood, Eran; Raymond, Peter A.; Stubbins, Aron; Spencer, Robert G.M. (Environmental Science & Technology, 2015)
Dissolved organic carbon (DOC) plays a fundamental role in the biogeochemistry of glacier ecosystems. However, the specific sources of glacier DOC remain unresolved. To assess the origin and nature of glacier DOC, we collected snow from 10 locations along a transect across the Juneau Icefield, Alaska extending from the coast toward the interior. The Δ14C-DOC of snow varied from −743 to −420‰ showing progressive depletion across the Icefield as δ18O of water became more depleted (R2 = 0.56). Older DOC corresponded to lower DOC concentrations in snow (R2 = 0.31) and a decrease in percent humic-like fluorescence (R2 = 0.36), indicating an overall decrease in modern DOC across the Icefield. Carbon isotopic signatures (13C and 14C) combined with a three-source mixing model showed that DOC deposited in snow across the Icefield reflects fossil fuel combustion products (43–73%) and to a lesser extent marine (21–41%) and terrestrial sources (1–26%). Our finding that combustion aerosols are a large source of DOC to the glacier ecosystem during the early spring (April–May) together with the pronounced rates of glacier melting in the region suggests that the delivery of relic DOC to the ocean may be increasing and consequently impacting the biogeochemistry of glacial and proglacial ecosystems in unanticipated ways.